EVALUATION OF THE ECO LIFESTYLE FOOTPRINT IN ROMANIA - Valentina-Mariana Manoiu; Alexandru-Codrut Miroiu; Alexandru-Ioan Craciun (European Scientific Journal, ESJ, 2014)
The sustainable eco-lifestyle is progresingly becoming part of the mainstream thinking. This paper evaluates the ecological footprint of a specific type of vegan eco-lifestyle adopted by one of the authors, and compares it to that of a typical Bucharest citizen. Although the activities of the eco lifestyle are reflected by individual actions and choices, its effects are substantial when adopted on a large scale. If the entire population would pick up on the lifestyle of the eco-citizen, human needs would only require the resources of 0.78 planets; however, should mankind choose to adopt the other respondent’s lifestyle, 1.96 planets would be needed. According to the conclusions presented in the study, the adoption of these environmentfriendlier vegan and vegetarian lifestyles by the majority of the population can be an effective way to diminish the burden directed onto the ecosystems that our planet is depending on. The summarized version of this extensive study has been presented at the Global Conference on Environmental Studies, April 2014, Rome, Italy.